PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA VIDEO EDUKASI TERHADAP PENGETAHUAN DAN SIKAP MENGENAI SKINCARE BER-BPOM PADA GENERASI Z DI SMKN 6 PEKANBARU - Draini, Osi; Gustianingsih, Febri (Ensiklopedia of Journal, 2025)
Abstract: Skincare with dangerous ingredients can trigger skin damage or other diseases for consumers who use it. The purpose of this study was to determine the effect of health education using educational video media on knowledge and attitudes in Generation Z regarding BPOM skincare. This research was conducted at SMKN 6 Pekanbaru. The research design used was Quasi Experiment with one group pre-test post test design. The sampling technique used a “purposive sampling” technique with a total of 51 respondents. Data collection tools were using questionnaires that were analyzed univariately and bivariately with the Wilcoxon Non Parametric test. The results of this study showed that the mean level of knowledge before the intervention was given was 8.47. Mean knowledge after being given was 11.24. While the attitude of Generation Z before being given the intervention obtained a mean of 16.90. The mean attitude after the intervention was 22.18. There is an effect of health education using educational video media at SMKN 6 with a p value of 0.000. It is expected that Generation Z can increase knowledge and can change attitudes about BPOM skincareKeywords: BPOM-approved skincare, Knowledge and attitude, Generation Z